SINERGITAS ORANG TUA, GURU DAN PELAYAN GEREJA DALAM PROSES PERKEMBANGAN MORAL REMAJA DI ERA DISRUPSI - Irene Preisilia Ilat; Marthin Dani Martoyo (TENTIRO: Jurnal Pendidikan dan Kesehatan, 2024)
The era of disruption affects the moral development process of today's youth so that synergy between parents, teachers and church ministers is needed. The fact that there is still a lack of synergy between parents, teachers and church ministers in the moral development of adolescents is because parents fully entrust their children's education at school or church. The busyness of parents in working is one of the causes of the lack of parental control over the experiences that children get at school or in church while the educational process at school and in church is limited by time. Based on this problem, the purpose of this study is to see what the synergy of parents, teachers and church ministers looks like in the process of adolescent moral development in the era of disruption. Qualitative research with descriptive method was chosen in this research. The informants in this study are parents, Christian Religious Education teachers and church servants or youth coaches. Data were collected through field observations, interviews with respondents and collecting supporting documents. The results of this study show that the form of synergy between parents, teachers and church ministers has been implemented through coordination and communication between parents and teachers, the formation of a parents' association at school, parents fully support the involvement of teenagers in church activities, and church ministers equip teachers through seminars or workshops on deepening understanding of the Word of God to face the process of moral development of adolescents in the era of disruption.